Targeted Therapies in Lung Cancer - Pirker, Robert; Filipits, Martin (Current Pharmaceutical Design, 2009)
Targeted therapies have improved and will continue to improve the outcome of lung cancer. Current strategies focus on the blockade of growth factor receptors and the inhibition of angiogenesis. Epidermal growth factor receptor (EGFR)-directed tyrosine kinase inhibitors (TKIs) have already been established as a treatment option in patients with advanced non-small cell lung cancer (NSCLC) progressing after prior treatment with chemotherapy. EGFR-directed monoclonal antibodies in combination with platinum-based first-line chemotherapy have shown promising efficacy in phase II trials. In a phase III trial, cetuximab combined with cisplatin/vinorelbine resulted in superior survival compared to chemotherapy alone in patients with advanced EGFR-positive NSCLC. Inhibition of angiogenesis has also been successfully applied as a new treatment strategy. Bevacizumab added to palliative chemotherapy has improved progression-free survival in two phase III trials and overall survival in one of these trials in selected patients with advanced non-squamous cell lung cancer. Bevacizumab is now approved for selected patients with advanced NSCLC in combination with platinum-based chemotherapy. Other targeted therapies including dual and multi-kinase inhibitors are in earlier stages of clinical development. In small cell lung cancer (SCLC), targeted therapies have also been studied but no clinical benefit could be demonstrated for these agents.
Keywords: Targeted therapy